Towards a New Learning Paradigm for Mobile, Open and Social 10Second Languages - Bárcena, Elena (2020)
This article explores the design and development of an innovative didactic paradigm for second 12languages at a distance, social and open (with a triple linguistic, methodological and technological 13dimension), whose core is defined by mobile technology and the Learning of Languages Assisted 14by Mobile or MALL, not only as an additional tool that can be used to perform certain tasks (in a 15more or less structured way), but asthe main way in which distance students of second languages 16can interact and carry out their learning in a way effective.